2010
DOI: 10.1002/jid.1748
|View full text |Cite
|
Sign up to set email alerts
|

‘Youthscapes’ and escapes in rural Africa: Education, mobility and livelihood trajectories for young people in Eastern Cape, South Africa

Abstract: This paper draws attention to the significance of mobility in shaping the educational and livelihood trajectories of rural young people in sub-Saharan Africa, with particular reference to a case study in Eastern Cape, South Africa. Young rural people commonly face both economic and political exclusions. As our case study illustrates, in the context of work demands, restricted basic education and poverty, the potential for escape, whether to secondary education or city jobs, is limited and in some respects high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…Yet, from their different family, class and socio-economic positions they have perspectives diametrically opposed on the role of privatization in realizing such aspirations. More consistent with the literature on youth and rural transformation, which has identified a strong lack of interest among the young generation in rural farming and rural futures, there are also young people in Elangata Wuas who do not aspire to pastoralism (Porter et al, 2010;White, 2012). Claudia (Class VII) shares her non-pastoral, nonrural aspirations during a follow-up interview:…”
Section: The Intersectionality Of Young Perspectivessupporting
confidence: 59%
“…Yet, from their different family, class and socio-economic positions they have perspectives diametrically opposed on the role of privatization in realizing such aspirations. More consistent with the literature on youth and rural transformation, which has identified a strong lack of interest among the young generation in rural farming and rural futures, there are also young people in Elangata Wuas who do not aspire to pastoralism (Porter et al, 2010;White, 2012). Claudia (Class VII) shares her non-pastoral, nonrural aspirations during a follow-up interview:…”
Section: The Intersectionality Of Young Perspectivessupporting
confidence: 59%
“…Being employed is a means of economic survival for refugees and asylum-seekers, who have very little additional resources on which to rely, or government assistance to carry them through difficult times (Peberdy, Crush & Msibi, 2004). A large proportion (61 per cent) of the refugees and asylum-seekers in the sample found employment in either the formal or informal sector or as casual workers, even though research by Porter, Hampshire, Mashiri, Dube & Maponya (2010) showed that migrants are exposed to economic and political exclusion. This reflects their urgency and need to find employment.…”
Section: Results On the Estimated Ols And Ordered Probit Modelsmentioning
confidence: 96%
“…For example, there are growing literatures on the role of agrarian issues in motivating and sustaining young people's participation in the Sierra Leone conflict (Peters and Richards 2011;Richards 2005Richards , 2011Fanthorpe and Maconachie 2010) and the impacts of transportation on livelihood decisions of rural young people (Porter 2010;Porter et al 2011;Porter et al 2010). There is also a literature on migration behaviour of rural young people that is highly relevant (Barratt et al 2012;van Dalen et al 2005;Tacoli and Mabala 2010).…”
Section: In This Ids Bulletin)mentioning
confidence: 99%